Pengaruh Current Ratio, Earning Per Share, Debt Equity Ratio, dan Return On Equity Terhadap Kebijakan Deviden (Dividend Payout Ratio) Studi Pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia - Witaradya E. S, Morris; wati, Andar (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
Background of this research aimed to determine the effect of independent variables, consisting of the Current Ratio, Earnings Per Share, Debt Equity Ratio, and Return On Equity of the dividend policy of a company, as a dependent variable, either simultaneously, or partially, and to find out which of the independent variables are the most dominant effect on the dividend policy.Objects in this study is manufacturing companies listed in Indonesia Stock Exchange, with a period of study in 2010-2011. Type of this research is is explanotory Research, which describes whether there is influence between the variables under study through a hypothesis testing performed. This research sampling are using with census method with criteria which consists of 41 companies. Data analysis tool used is the Multiple Linear Regression.The resultsÂ of this researchÂ showed simultaneous independent variables researched affect dividend policy on a sample of manufacturing firms. And partially, only variables Eraning Per Share and Debt to Equity Ratio which hasÂ a significant impact on dividend policy on a sample of manufacturing firms. While the variable current ratio and return on equity has no significant effect on dividend policy. Variable Earning Per Share has the most dominant effect on the dividend policy of the company.Keyword: Dividend Payout Ratio, Current Ratio, Earning Per Share, Debt Equity Ratio, and Return On Equity